2013
DOI: 10.1038/ejcn.2013.180
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of violent video-game playing on blood pressure and appetite perception in normal-weight young men: a randomized controlled trial

Abstract: Watching television and playing video game being seated represent sedentary behaviours and increase the risk of weight gain and hypertension. We investigated the acute effects of violent and non-violent video-game playing on blood pressure (BP), appetite perception and food preferences. Forty-eight young, normal-weight men (age: 23.1±1.9 years; body mass index: 22.5±1.9 kg/m(2)) participated in a three-arm, randomized trial. Subjects played a violent video game, a competitive, non-violent video game or watched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 9 publications
3
33
1
1
Order By: Relevance
“…Movie types did not seem to affect directly hunger or appetite but rather triggered some food preferences, such as a preference for sweet after a romance movie, which was the opposite for a horror movie. Those results are different from the previous results by Sievro et al 6 in which they showed that men who played violent games had a higher preference for sweet foods. The difference can be explained by two hypotheses: first, in our study there was no randomization (only convenient sampling), which means that we are not sure whether the people who prefer sweet usually pick romanticcomedy movies and people who prefer fatty or salty food usually pick violent/thriller movies.…”
Section: Resultscontrasting
confidence: 81%
See 2 more Smart Citations
“…Movie types did not seem to affect directly hunger or appetite but rather triggered some food preferences, such as a preference for sweet after a romance movie, which was the opposite for a horror movie. Those results are different from the previous results by Sievro et al 6 in which they showed that men who played violent games had a higher preference for sweet foods. The difference can be explained by two hypotheses: first, in our study there was no randomization (only convenient sampling), which means that we are not sure whether the people who prefer sweet usually pick romanticcomedy movies and people who prefer fatty or salty food usually pick violent/thriller movies.…”
Section: Resultscontrasting
confidence: 81%
“…Our study, which completes previous work by Sievro et al 6 on violence in video games, elucidates the acute effect of violence and its consequent stress on food intake and preferences in a reallife setting. Our study is a step forward going beyond the classical energy balance theory for explaining obesity.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…2 In 2012-2013, the GP Patient Survey obtained 0.97 million responses, corresponding to approximately 2% of the English population. 3 Although the response rate was relatively low (35%), a weighting scheme was applied to the responses to account for the possibility of nonresponse bias and ensure representativeness of the eligible population. 3 A simulated patient study similar in design to that reported by Rhodes et al 4 has demonstrated the construct validity of measures of access derived from the GP Patient Survey.…”
Section: Access To Primary Care In Englandmentioning
confidence: 99%
“…3 Although the response rate was relatively low (35%), a weighting scheme was applied to the responses to account for the possibility of nonresponse bias and ensure representativeness of the eligible population. 3 A simulated patient study similar in design to that reported by Rhodes et al 4 has demonstrated the construct validity of measures of access derived from the GP Patient Survey. 5 Compared with the results presented by Rhodes et al, 4 wait times for appointments in England are typically shorter than in the sampled US states, for both privately insured and Medicaid patients.…”
Section: Access To Primary Care In Englandmentioning
confidence: 99%